An Analysis of Expletive Words Used in Conversation by Kubang Society, Pauh Sub District, Padang - Muthia Damaiyanti; Edwar Kemal (Politeknik Negeri Padang, 2013)
Speaking is one of the activities conducted by human everyday. In speaking, the sentences can be simple sentences and even complex sentences. Sometimes, in speaking the words and phrases are used to fill a syntactic position without having a meaning or referent. It is called expletive. The research analyzes the form and function of expletive in utterances of kubang society. The data were collected through interviews and recording technique and the theory used from Azar and Manser. The data were presented in written form. The research shows that there are fiften expletive words used by Kubang society in conversation. Expletive often appears in adverb. Though, it is only a filler, expletive words are often used by Kubang society.